2022
DOI: 10.1097/inf.0000000000003523
|View full text |Cite
|
Sign up to set email alerts
|

Pasteurella multocida Bacterial Meningitis in a 33-Day-Old Infant

Abstract: A 33-day-old previously healthy term female is admitted to the pediatric intensive care unit with fever, lethargy and bulging fontanel. Given concern for meningitis, a lumbar puncture is performed and empiric treatment is initiated. The cerebrospinal fluid culture results reveal Pasteurella multocida. The patient is treated with intravenous ampicillin for 3 weeks and discharged with close outpatient follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…While infections caused by P. multocida in humans are well documented ( 14 , 35 37 ), little is known about the mechanisms involved. Our recent work revealed that P. multocida isolates from different animals demonstrate the capacities to adhere to and invade human respiratory epithelial cells (BEAS-2B) ( 25 ).…”
Section: Discussionmentioning
confidence: 99%
“…While infections caused by P. multocida in humans are well documented ( 14 , 35 37 ), little is known about the mechanisms involved. Our recent work revealed that P. multocida isolates from different animals demonstrate the capacities to adhere to and invade human respiratory epithelial cells (BEAS-2B) ( 25 ).…”
Section: Discussionmentioning
confidence: 99%
“…While infections caused by P. multocida in humans is well documented (16,(35)(36)(37), little is known about the mechanisms involved. Our recent work revealed that P. multocida isolates from different animals demonstrate capacities of adhering and invading the human respiratory epithelial cells (BEAS-2B) (20).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Pm can be transmitted by mosquitoes, flies, or blood-sucking insects or by direct bites by cats, dogs, and other animals (2,3). It has even been reported that people might be infected by ill animals in an unknown manner, highlighting its potential threat to human health (4)(5)(6)(7). These diseases have caused huge economic losses to the cattle industry because of increased mortality, high treatment costs, reduced growth rate, and poor carcass quality (8).…”
Section: Introductionmentioning
confidence: 99%